Study of Agrometeorological Indices as Affected by Different Duration Rice Varieties and Crop Establishment Methods - Jagtap, D. N.; Sutar, M. W.; Mahadkar, U. V.; Chavan, S. A.; Pinjari, S. S.; Jadhav, M. S. (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted on Agronomy farm, College of Agriculture, Dapoli, Maharashtra, India during kharif (June)2015 and 2016 to study of agrometeorological indices as affected bydifferent duration rice varieties and crop establishment methods. The experiment was laid out according to split plot design with three replications. Twenty four treatment combinations comprised of four main plot treatments: Drilling, Early transplanting (15 days after sowing), Transplanting as per recommendation (21 days after sowing) and Transplanting with Thomba method (under insufficient rain water for puddling, this method usually preferred. In this case transplating has been completed without puddling. With the help ofpointed bamboo stick holes has been made and seedlings inserted into that holes) and six subplot treatments Karjat-184, Palghar-1, Karjat-2, Sahyadri-2, Karjat-3 and Karjat-7. To obtain higher yield from kharif rice, crop should to be established by transplanting method with variety Sahyadri-2 followed by Karjat-7. However, early transplanting and Thomba methods are the alternatives to conventional transplanting method. Because with Thomba method we can complete transplanting of rice even if insufficient rainwater is there for puddling and get the better yield comparatively. The highest GDD, Hydrothermal units and Helio-thermal units required by Karjat-2 variety, while higher Heat use efficiency and Helio-thermal use efficiency recorded by Sahyadri-2 variety.